Perlindungan Hukum Perwakilan Diplomatik Di Negara Penerima Yang Dikategorikan Sebagai Negara Rawan Konflik Berdasarkan Hukum Internasional - Zaidan Nabil Musyaffa; Dodik Setiawan Nur Heriyanto (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to determine and examine international law governing the legal protection of diplomatic representatives sent to countries categorized as conflict-prone areas. The main issues studied are how legal protection is provided to diplomatic representatives sent to countries categorized as conflict-prone areas and how the receiving state is accountable to diplomatic representatives who suffer any losses while on duty. This study uses a legislative and conceptual approach, by examining regulations related to this research. The study was conducted by analyzing actual conditions in accordance with the provisions of the 1961 Vienna Convention on Diplomatic Law. The results show that the 1961 Vienna Convention does not explain the granting of special treatment in order to provide protection for diplomatic representatives assigned to conflict-prone countries. The responsibility of the receiving state is explained in the optional protocol, but does not provide a concrete form of the intended responsibility. Special treatment for diplomats is found in several regulations made by the sending state, while the concrete form of the receiving state's responsibility is found in the Draft Articles Responsibility of States for Internationally Wrongful Acts.